Sensing and monitoring in tunnels testing and monitoring methods for the assessment of tunnels. (3rd March 2020) - Strauss, Alfred; Bien, Jan; Neuner, Hans; Harmening, Corinna; Seywald, Christian; Österreicher, Michael; Voit, Klaus; Pistone, Elisabetta; Spyridis, Panagiotis; Bergmeister, Konrad
Abstract: The paper presents a review of testing methods and a classification of strategies and tools in terms of technologies and techniques applied to the monitoring of tunnels. In particular, the topic is contextualized through a brief introduction in Chapter 1, followed by defect taxonomy and degradation mechanisms in Chapters 2 and 3, respectively. Chapters 4 and 5 are related to monitoring strategies and technologies. The former consists of purpose‐based categorization of monitoring policies, while the latter consists of classification of monitoring methods including nondestructive and semidestructive techniques as well as of classification of various types of sensors also based on the physical or chemical quantity measured. General rules of implementation and operation of tunnel monitoring systems are presented taking into account international expert knowledge as well as contemporary practical experience in Austria. Considered issues are related to the fib Model Code 2020 (MC2020) focused on evaluation of structural performance assisted by monitoring and testing. Chapter 6 presents challenges related to the monitoring implementation and operation. Chapter 7 discusses about monitoring characteristics in new tunnel, including data acquisition‐transmission and specific monitoring techniques. Chapter 8 instead treats a particular topic related to considerations related to monitoring characteristics of existing tunnel under investigation. Concluding remarks and references finally close the paper.